The Kinetics of Calcium Oxide Catalyzed Esterification of Glycerol with Free Fatty Acids Using Pseudo-homogeneous Model Approach - Megawati Megawati; Dhoni Hartanto; Catur Rini Widyastuti; Diyah Saras Wati; Eny Nurhayati (Reaktor, 2018)
Abstract This research aims to study the reaction kinetics of esterification reaction of glycerol with free fatty acid (FFA) using calcium oxide catalyst to produce mono-diacylglycerol (MDAG) using pseudo-homogeneous approach. The effects of time and temperature on the reaction conversion were investigated simultaneously. The FFA used was from the waste of cocoa production process, while the solid catalyst used was calcium oxide from eggshell ash. The results show that the cocoa based FFA was composed of palmitic acid (49.24%), methyl stearate (1.05%), oleic acid (25.39%), and stearic acid (24.32%). The calcium oxide content in the eggshell ash was 60% w/w. At all temperatures studied (60, 70, and 80oC), as the reaction time increased, the conversion increased sharply in the first 5 minute followed by a gradual raise to an almost constant value after 20 minutes (0.844; 0.845; and 0.854, respectively). Pseudo-homogeneous second order model can describe the reaction kinetics satisfactorily. The reaction constants (k) at 60, 70, and 80oC were 0.00384, 0.003401, and 0.003518 (L/mole.minute), respectively. The effects of temperature on reaction rate obey the Arrhenius’ equation with collision factor (A) is 0.2659 (L/mole.minute) and activation energy (Ea) is 3544 J/mol. Keywords: calcium oxide; free fatty acid; glycerol; pseudo-homogeneous approach